2009
DOI: 10.1007/s11069-009-9382-3
|View full text |Cite
|
Sign up to set email alerts
|

Developments in storm tide modelling and risk assessment in the Australian region

Abstract: An overview is provided of some of the significant storm tide modelling and risk assessment studies undertaken over the past few years within Australia and the nearby oceanic regions for government and industry. Emphasis is placed on the need for integrated planning and forecasting approaches for storm tide risk assessment. The importance of the meteorological forcing and the appropriate modelling of each of the storm tide components, namely, astronomical tide, storm surge, breaking wave setup and coastal inun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 8 publications
(8 reference statements)
0
9
0
Order By: Relevance
“…Results reported in Harper et al (2009) showed that a 10% increase in tropical cyclone intensity produced only a small increase in the 1-in-100 year storm tide, but a larger increase in 1-in-1000 year storm tides.…”
Section: Projected Changes To Extreme Sea Levelsmentioning
confidence: 96%
“…Results reported in Harper et al (2009) showed that a 10% increase in tropical cyclone intensity produced only a small increase in the 1-in-100 year storm tide, but a larger increase in 1-in-1000 year storm tides.…”
Section: Projected Changes To Extreme Sea Levelsmentioning
confidence: 96%
“…Like the US east coast, Australia has a long history of coastal flooding associated with tropical cyclones, with several major events recorded since the late 1880s (Harper et al 2009). The largest death toll of any natural disaster in Australian history occurred in March 1899 when cyclone Mahina hit Bathurst Bay (Queensland), claiming the lives of over 300 people (Nott and Hayne 2000).…”
Section: Australiamentioning
confidence: 99%
“…Several approaches have been proposed so far, such as JPM-OS (Joint Probability Methods with Optimal Sampling, e.g., Resio, 2007;Toro et al, 2010) or the statistical-deterministic model of Emanuel et al (2006). They have been used successfully for storm surge assessment at local (Lin et al, 2010(Lin et al, , 2012, regional (Harper et al, 2009;Niedoroda et al, 2010) or even continental (Haigh et al, 2014) scales. In the present paper, we use the statistical-deterministic approach of Emanuel et al (2006), which provided good results for Guadeloupe in a previous study (Krien et al, 2015).…”
Section: Methodsmentioning
confidence: 99%